Welfare Costs of Inflation in a Dynamic Economy with Search Unemployment and Endogenous Growth - Burkhard Heer (Center for Economic Studies and ifo Institute (CESifo), 2000)
Recent work on money and endogenous growth finds modest welfare costs of inflation. Furthermore, high inflation reduces the growth rate. We present a monetary endogenous growth model with labor market frictions in the form of search unemployment which is calibrated for the US economy. Interestingly, both employment and the growth rate may even increase with the rate of inflation depending on the elasticity of labor supply. Considering the transition dynamics following a change in the monetary policy, the optimal quarterly inflation rate is found to amount to approximately 3.5% in the benchmark case. A reduction of the inflation rate from its optimal value to zero results in a welfare loss equal to 0.3% of total consumption.
Keywords: 330; Welfare costs of inflation; money demand; search unemployment; endogenous growth; transistion dynamics